2011
DOI: 10.1021/ef2010139
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Fuels from Biomass for Homogeneous Low-Temperature Diesel Combustion

Abstract: The use of modern biofuels in mobile applications has an enormous potential to reduce greenhouse gases as well as engine pollutant emissions, such as soot or nitrogen oxides. This beneficial effect is directly related to the molecular structure of the biofuel as a product of an optimized production process. To understand the influence and emission reduction potential of the large variety of different fuel properties, this study aims to identify desirable fuel characteristics and define optimized biofuel compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 35 publications
0
67
0
3
Order By: Relevance
“…furans and alcohols) are favourable in terms of the PM/NO X trade-off, which is often referred to as the 'Diesel-dilemma'. 7,26,27 The combination of a high oxygen content of the fuel candidates and low ignitability might cause lower equivalence ratios at the start of combustion and thus lower soot emissions at an equal NO X level compared to fossil fuels. Due to the reduced reactivity of 1-octanol in combination with the boiling point at the lower end of the diesel distillation curve and the higher oxygen content of ;12.3% m/m, 1-octanol appears to be a promising candidate for combustion in CI engines.…”
Section: Tmfb For Clean Diesel-type Combustionmentioning
confidence: 99%
“…furans and alcohols) are favourable in terms of the PM/NO X trade-off, which is often referred to as the 'Diesel-dilemma'. 7,26,27 The combination of a high oxygen content of the fuel candidates and low ignitability might cause lower equivalence ratios at the start of combustion and thus lower soot emissions at an equal NO X level compared to fossil fuels. Due to the reduced reactivity of 1-octanol in combination with the boiling point at the lower end of the diesel distillation curve and the higher oxygen content of ;12.3% m/m, 1-octanol appears to be a promising candidate for combustion in CI engines.…”
Section: Tmfb For Clean Diesel-type Combustionmentioning
confidence: 99%
“…Recently, several 2nd generation biofuels were shown to be highly beneficial for use in combustion engines [5,6]. At the same time, it was shown that blending of biofuels further improves the performance.…”
Section: Introductionmentioning
confidence: 99%
“…There is little to no soot formation observable during its combustion in a compression ignition engine [6].…”
Section: Introductionmentioning
confidence: 99%
“…The P-series fuels are blends of ethanol, 2-MTHF, pentanes, and butane that can be used in severe cold-weather conditions to solve engine cold-start issues. Janssen et al 39 recently reported a blend of 2-MTHF with di-n-butylether complies with ideal fuel properties in terms of emission performance and engine efficiency.…”
Section: Introductionmentioning
confidence: 99%